2016
DOI: 10.14393/bj-v32n3a2016-33210
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease as a risk factor for aspiration pneumonia: a systematic review

Abstract: Academics. Inclusion criteria included randomized clinical trials, case-control and cohort studies, as well as cross sectional studies, in Portuguese and English. Teams of reviewers, independently and in duplicate, screened titles and abstracts of full text articles to determine eligibility. The selected articles were read in full and the variables evaluated independently and described in predetermined forms according to clinical outcomes. As a result, five studies out of 653 publications were included: three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Periodontitis is an important public health problem and needs to be measured and evaluated as a clinical entity, that is, the role of periodontitis in asthma, COPD, or pneumonia. Many previous systematic reviews (Cagnani et al, 2016;Ferreira et al, 2019;Mendes et al, 2018;Moraschini et al, 2018;Shi et al, 2018;Tan et al, 2016;Zeng et al, 2012) presented their conclusions only on the basis of the relationship between one or more periodontal clinical parameter with the abovementioned respiratory diseases, which is different from the main objective of this review.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Periodontitis is an important public health problem and needs to be measured and evaluated as a clinical entity, that is, the role of periodontitis in asthma, COPD, or pneumonia. Many previous systematic reviews (Cagnani et al, 2016;Ferreira et al, 2019;Mendes et al, 2018;Moraschini et al, 2018;Shi et al, 2018;Tan et al, 2016;Zeng et al, 2012) presented their conclusions only on the basis of the relationship between one or more periodontal clinical parameter with the abovementioned respiratory diseases, which is different from the main objective of this review.…”
Section: Discussionmentioning
confidence: 93%
“…The main findings of this systematic review showed a moderate to strong association between periodontitis and respiratory diseases, with high methodological quality among most of the studies and low to moderate heterogeneity of the selected investigations. Previous systematic reviews related to the association between periodontal clinical parameters and asthma (Ferreira et al, 2019;Mendes et al, 2018;Moraschini et al, 2018); worse periodontal condition and COPD (Shi et al, 2018;Tan et al, 2016;Zeng et al, 2012); and periodontal disease and pneumonia (Cagnani et al, 2016) showed a positive relationship between periodontal clinical parameters and the respiratory disease of interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in critically ill patients due to weakness and hospitalization, oral hygiene is impaired, which exacerbates dysbiosis [70][71][72]. Several systematic reviews indicated a positive association between poor oral hygiene and oral care interventions in nursing home and hospital patients [73][74][75].…”
Section: Biomed Research Internationalmentioning
confidence: 99%